2021
DOI: 10.3390/ijms22105284
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Perilipin 5 in Non-Alcoholic Fatty Liver Disease and Its Role in Hepatocellular Carcinoma: A Review of Novel Insights

Abstract: Consumption of high-calorie foods, such as diets rich in fats, is an important factor leading to the development of steatohepatitis. Several studies have suggested how lipid accumulation creates a lipotoxic microenvironment for cells, leading cells to deregulate their transcriptional and translational activity. This deregulation induces the development of liver diseases such as non-alcoholic fatty liver disease (NAFLD) and subsequently also the appearance of hepatocellular carcinoma (HCC) which is one of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 101 publications
0
16
0
1
Order By: Relevance
“…However, we observed a downregulation of PLIN5 gene expression following irradiation that was fostered by the combined treatments. It has been shown that PLIN5 protects against lipotoxicity mainly in oxidative tissues [ 6 , 41 ], thus the downregulation observed with the combined treatments may indicate a reduced ability of the cells to deal with the oxidative stress, which, in turn, could be implicated in increased radiosensitization. It is worth noting that, as expected, PF-06424439 treatment significantly reduced the transcript levels of DGAT2, which were further decreased by the combined treatment soon after IR.…”
Section: Discussionmentioning
confidence: 99%
“…However, we observed a downregulation of PLIN5 gene expression following irradiation that was fostered by the combined treatments. It has been shown that PLIN5 protects against lipotoxicity mainly in oxidative tissues [ 6 , 41 ], thus the downregulation observed with the combined treatments may indicate a reduced ability of the cells to deal with the oxidative stress, which, in turn, could be implicated in increased radiosensitization. It is worth noting that, as expected, PF-06424439 treatment significantly reduced the transcript levels of DGAT2, which were further decreased by the combined treatment soon after IR.…”
Section: Discussionmentioning
confidence: 99%
“…PLIN5 is a promising therapeutic target for NAFLD and atherosclerosis, and possibly for some other metabolic diseases. We wish to redirect interested readers to recent reviews for further information about the role of PLIN5 and mitochondria-LD contact sites in the development of NAFLD and other diseases [109,110].…”
Section: Role Of Perilipin 5 In Nafld and Atherosclerosismentioning
confidence: 99%
“…PLIN4 has been implicated in stabilizing the LD by interacting directly with TG moieties when their phospholipid coverage is limited [ 8 ]. PLIN5 appears to be involved in protective roles against mitochondrial damage and endoplasmic reticulum stress in liver [ 9 ].…”
Section: Lipid Droplet Biogenesis General Aspectsmentioning
confidence: 99%